Penanggulangan estetik dengan porcelain laminate veneers pada diskolorasi gigi depan rahang atas Overcoming esthetic with porcelain laminate veneers on discolorisation of anterior maxillary teeth - Eni Rahmi; Deddy Firman; Hasna Dziab (Journal of Dentomaxillofacial Science, 2013)
In modern dentistry, porcelain laminate veneers have become ultimate option of tooth rehabilitation for improvedesthetics performance. The demand to have better smile and beautiful face pushed patient to visit dentist byrehabilitating functional and esthetic, especially anterior tooth. Characteristics of porcelain measuring up to opticproperties, biocompatibiliy and resistance could give satisfying result on a long term. Transformation, size measure,tooth position and colour can be achieved by minimal preparation of minimum tooth structure. This paper describedcase selection and proper manipulation technique in determining efficacy of treatment with porcelain laminateveneers.